The role of schools in children and young people's self-harm and suicide: systematic review and meta-ethnography of qualitative research. (December 2016) - Evans, Rhiannon; Hurrell, Chloe
Abstract Background Evidence reports that schools influence children and young people's health behaviours across a range of outcomes. However there remains limited understanding of the mechanisms through which institutional features may structure self-harm and suicide. This paper reports on a systematic review and meta-ethnography of qualitative research exploring how schools influence self-harm and suicide in students. Methods Systematic searches were conducted of nineteen databases from inception to June 2015. English language, primary research studies, utilising any qualitative research design to report on the influence of primary or secondary educational settings (or international equivalents) on children and young people's self-harm and suicide were included. Two reviewers independently appraised studies against the inclusion criteria, assessed quality, and abstracted data. Data synthesis was conducted in adherence with Noblit and Hare's meta-ethnographic approach. Of 6744 unique articles identified, six articles reporting on five studies were included in the meta-ethnography. Results Five meta-themes emerged from the studies. First, self-harm is often rendered invisible within educational settings, meaning it is not prioritised within the curriculum despite students' expressed need. Second, where self-harm transgresses institutional rules it may be treated as 'bad behaviour', meaning adequate support is denied. Third, schools' informal management strategy of escalating incidents of self-harm to external 'experts' serves to contribute to non-help seeking behaviour amongst students who desire confidential support from teachers. Fourth, anxiety and stress associated with school performance may escalate self-harm and suicide. Fifth, bullying within the school context can contribute to self-harm, whilst some young people may engage in these practices as initiation into a social group. Conclusions Schools may influence children and young people's self-harm, although evidence of their impact on suicide remains limited. Prevention and intervention needs to acknowledge and accommodate these institutional-level factors. Studies included in this review are limited by their lack of conceptual richness, restricting the process of interpretative synthesis. Further qualitative research should focus on the continued development of theoretical and empirical insight into the relationship between institutional features and students' self-harm and suicide.